Molecular and morphological identification of Argyrops and Acanthopagrus (Sparidae) in the Java Sea, Indonesia - AGUS NURYANTO; FABIAN RIZKY FATHURAHMAN; DIAN BHAGAWATI; ERWIN RIYANTO ARDLI; DWI NUGROHO WIBOWO; ATANG ATANG (Society for Indonesian Biodiversity, 2026)
Abstract. Nuryanto A, Fathurahman FR, Bhagawati D, Ardli ER, Wibowo DN, Atang. 2026. Molecular and morphological identification of Argyrops and Acanthopagrus (Sparidae) in the Java Sea, Indonesia. Biodiversitas 27 (5): d270508. https://doi.org/10.13057/biodiv/d270508. Accurate species identification is fundamental to effective fisheries management and understanding of marine biodiversity. Previous morphological records have reported Argyrops spinifer from Indonesian waters, including the Java Sea, Indonesia, while recent molecular evidence from southern Java identified Argyrops bleekeri. These inconsistencies highlight the need for integrative taxonomic approaches. This study aimed to evaluate sparid diversity along the northern coast of Java Island using morphological examination and DNA barcoding of the mitochondrial cytochrome c oxidase subunit I (COI) gene. Fish specimens were collected from four landing sites (Pekalongan, Cirebon, Indramayu, Karawang) along the Java Sea. A total of 31 specimens were examined, comprising 15 Acanthopagrus and 16 Argyrops. High-quality COI sequences were obtained from 30 specimens (96.8% success rate). Molecular identification assigned all Acanthopagrus specimens to Acanthopagrus pacificus (n:15). Among Argyrops, 14 specimens were identified as A. bleekeri, while only one specimen was identified as A. spinifer, representing just 6.7% of Argyrops samples. Genetic similarity values (99.04-100%) and low intraspecific K2P distances (0.0027-0.0036) confirmed species-level assignments, while phylogenetic analysis supported clear separation between taxa. The coexistence of A. bleekeri and A. spinifer at the Indramayu landing site provides the first molecular confirmation of A. spinifer in the Java Sea and demonstrates the limitations of morphology alone, as both species were indistinguishable based on external traits. These findings highlight the risk of species misidentification in fisheries data when relying solely on traditional taxonomy. Integrating molecular tools with morphological examination is therefore critical to avoid compromising stock assessments and biodiversity monitoring in Indonesian marine ecosystems.